DESIGN OF GIANT SEA-WALL BASED ON HYDRODYNAMICS CONDITION OF JAKARTA BAY - Aditya E, Rahmat
Jakarta faces the threat of loss of territory due to the intrusion of sea water. A massive groundwater loss results to rapid settlement. This is compounded by an increase in the load on the ground level as a result of the massive development. Due to the settlement, some areas of Jakarta has been under the sea level. In some hightide cases, some areas of Jakarta were inundated to a depth of 1 m. There needs to be a long term solution so that the amount of ground water that is taken can be reduced and the soil settlement does not happen too fast. Indonesia and the Dutch government established a masterplan of National Capital Integrated Coastal Development in term of Jakarta’s coastal area development, the construction of protective levees and reservoir that will supply fresh water to replace groundwater use. Protective levees in Jakarta was designed to be safe in receiving the hydrodynamic conditions in the vicinity. For the Jakarta area alone, the conditions that must be considered is tidal, wave height and sea level rise due to global warming. Under these provisions, the 13.83 m high embankment which is equipped with a wavereturn wall is needed with the crest elevation armor of +3.65 for overtopping method and +5.43 for run-up method. Based on the analysis of soil data, it is known that upper layer of soil dominating the Jakarta Bay area is very soft clay with the undrained shear strength of 7.55 kPa. This land has a quite large void ratio and is under normally consolidated condition. The consolidation settlement of soil is caused by its own weight and the traffic load, vi resulting on a decline in the peak elevation to LLWL by 2.95 m and increase the probability of overtopping with enormous discharge. Therefore, soil improvement is needed so that soil settlement is not too large. The utilized soil improvement method is stone-column, with a height of 8 m, a diameter of 1 m, and the spacing of 2 m. By using this method, occurring soil settlement is 1.1 m. This leads to a maximum road elevation below sea level, thus increasing road elevation of 1.5 m is needed. As a result, the height of seawall has to be adjusted into 15.5 m. Stone-column strengthening also raises the carrying capacity of the soil and enables it to receive stress due to deposition which is not more than 2 m at each stage. The number of dumping stages is 8, with the last imbankment height of 1.5 m. Those stages provide safety to the embankment slopes with avalanche safety factor of more than 1. Keyword: dikes, sea dikes, stone-column, soil degradation, soil reinforcement, soft ground, wave, diameter, spacing, elevation, consolidation, tides, sea level fluctuations